Value of SPECT/CT in the diagnosis of avascular necrosis of the head of femur: A meta-analysis. Issue 2 (May 2022) - Iqbal, B.; Currie, G.
Abstract: Introduction: To evaluate the diagnostic value of single photon emission computed tomography/computed tomography (SPECT/CT) in patients with avascular necrosis (AVN) of the femoral head. Methods: A search of the databases PubMed, ScienceDirect, and Google Scholar was undertaken using targeted index word. Studies satisfying inclusions and exclusions criteria were identified and additional related literature sources were considered. Analysis included pooled sensitivity and specificity, odds ratio (OR), and receiver operating characteristic (ROC) analysis. Results: Seven studies were identified that specifically related to the diagnostic accuracy of SPECT/CT in the detection or characterisation of AVN of the femoral head. These were included in the meta-analysis. The pooled sensitivity and specificity were 94% (95% confidence interval of 87–97%) and 75% (95% confidence interval of 68–81%) respectively, the OR was 44.5 (with a 95% confidence interval of 18.2–108.6), and the area under the SROC was 93.73% (with a 95% confidence interval of 89.2%–98.3%). Conclusion: This meta-analysis provides strong evidence of the high diagnostic efficacy of SPECT/CT in the evaluation of AVN of the femoral head. Implications for practice: In the absence of or contraindication to MRI, SPECT/CT is able to provide a suitable alternative for diagnosis of AVN of the head of femur.